Project Report on Urban Sprawel Pattern Recognition using Remote Sensing - ASWATHNARAYAN A and KAMAL G (2001)
INTERNAL GUIDE: MATHEW K K, MVJCE EXTERNAL GUIDE: T V RAMCHANDRA, IISC BANGALORE
Keywords: Remote Sensing